Directors' Monitoring Role, Ownership Concentration and Audit fees - Rabih Nehme; Amir Michael; Jim Haslam (Australasian Accounting, Business and Finance Journal, 2020)
The research objective is to analyse different factors potentially involved in influencing the size of audit fees. The association between the Board of Directors and the shareholders of listed companies should be effectively developed and there should be a higher spirit of compliance with the governance code. The empirical model is constructed to assess the theoretical and statistical relationship between audit fees and corporate governance characteristics over a period of four years (for FTSE 350 companies excluding financial institutions between 2012 and 2015). Different testing techniques are used for robustness reasons. We found that Board of Directors' characteristics are significant in relation to audit fees. Some of the Audit Committee characteristics are affected by the collegiality principle in relation to the Board of Directors' characteristics. The consultative role of audit committee directors is dominated by the role of the Board of Directors. Mandatory audit fees, and not total auditors' remuneration is included in this study. While other studies assess mainly one corporate governance mechanism in relation to audit fees, we include the corporate governance mechanisms that are directly related to auditors' scope. This paper can be used as a tool for audit practitioners and corporate executives to seek a better auditor-client relationship.
Keywords: Audit fees; External Auditors; Board of Directors; Audit Committees